PENINGKATAN MOTIVASI DAN HASIL BELAJAR BAHASA INGGRIS TENTANG PEMAHAMAN ISI BACAAN TEKS RECOUNT MELALUI METODE NHT PESERTA DIDIK KELAS VIII B SMP NEGERI 3 ADIWERNA - NUR ZUMROTI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2022)
This study aims to increase motivation and learning outcomes in the English subject for class VIII B Recount text at SMP Negeri 3 Adiwerna in the 2021/2022 academic year, using the NHT method. The type of research used was Classroom Action Research (CAR) which was carried out in two cycles to see the learning process and the improvement of student learning outcomes in participating in learning Recount text material through the NHT method. The subjects of this research were class VIII B students of SMP Negeri 3 Adiwerna, totaling 32 students. Data collection techniques in PTK consist of tests and non-tests. Data collected on each test and non-test activity from the implementation of each PTK cycle were analyzed descriptively using the percentage technique to see the learning process and the improvement of learning outcomes. The results of the study can be concluded with the learning model